1988
DOI: 10.1099/00221287-134-12-3285
|View full text |Cite
|
Sign up to set email alerts
|

Role of Outer-membrane Proteins and Lipopolysaccharide in Conjugation between Neisseria gonorrhoeae and Neisseria cinerea

Abstract: Little is known concerning the mechanism involved in cell contact between the donor and recipient during conjugation in Neisseria gonorrhoeae. The formation of stable mating pairs during conjugation in Escherichia coli appears to require a specific protein as well as LPS in the outer membrane of the recipient cell. To attempt to identify the cell surface components necessary for conjugation in the neisseriae, we began a comparison of the outer membrane of Neisseria cinerea strains that can (Con+) and cannot (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The state of the recipient cell membrane is a crucial factor affecting the formation of the junction bridge, thereby affecting conjugation transfer (Thomas and Nielsen, 2005). Genco and Clark (1988) reported that the outer membrane protein OmpA of the receptor bacteria can stabilize the junction bridge with the donor bacteria and promote the fertility of E. coli, S. typhimurium, and Neisseria cinerea. Sherburne and Taylor (1997) found that the deletion of lipid A synthesis genes rfaD and rfaE in S. typhimurium contributes to the truncation of lipid A, the reduction of porin by more than 90%, the change of cell membrane permeability, and the reduction of conjugation efficiency by 10-100 folds.…”
Section: Discussionmentioning
confidence: 99%
“…The state of the recipient cell membrane is a crucial factor affecting the formation of the junction bridge, thereby affecting conjugation transfer (Thomas and Nielsen, 2005). Genco and Clark (1988) reported that the outer membrane protein OmpA of the receptor bacteria can stabilize the junction bridge with the donor bacteria and promote the fertility of E. coli, S. typhimurium, and Neisseria cinerea. Sherburne and Taylor (1997) found that the deletion of lipid A synthesis genes rfaD and rfaE in S. typhimurium contributes to the truncation of lipid A, the reduction of porin by more than 90%, the change of cell membrane permeability, and the reduction of conjugation efficiency by 10-100 folds.…”
Section: Discussionmentioning
confidence: 99%
“…OM and LPS preparations at various concentrations (0; 0.5; 1.0; 2.0; 5.0; 10.0 and 15.0 μg) were added to a standard mating assay based on plasmid conjugal transfer [ 25 ], between the donor PA14Δ TnC2 ::Gm R and the recipient PAO1::Tc R . A mating mixture without the addition of OM or LPS was also included as a negative control for this experiment.…”
Section: Methodsmentioning
confidence: 99%